2022
DOI: 10.3390/soc12060174
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity Levels among University Students: A Cross-Sectional Study

Abstract: Background: University students may be vulnerable to food insecurity (FI) due to limited financial resources, lower purchasing power, and increasing housing and food costs. This study aimed to assess the prevalence and severity of FI and its associated factors among university students attending a public Portuguese university. Methods: A cross-sectional survey was designed, and data were collected using a self-reported online questionnaire validated for the Portuguese population. The study population included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…To date, FI among college and university students has received less attention in European countries than elsewhere. To our knowledge, research related to FI among European college/university student populations is currently limited, both before the pandemic [20] and in the context of the pandemic [21][22][23]. Nevertheless, there is direct, as well as indirect, evidence that FI and its attendant consequences are present in European universities.…”
Section: Introductionmentioning
confidence: 99%
“…To date, FI among college and university students has received less attention in European countries than elsewhere. To our knowledge, research related to FI among European college/university student populations is currently limited, both before the pandemic [20] and in the context of the pandemic [21][22][23]. Nevertheless, there is direct, as well as indirect, evidence that FI and its attendant consequences are present in European universities.…”
Section: Introductionmentioning
confidence: 99%
“…FI rate ranges between 38-34 % among college students whereas household rates were around 5-10% (12,34) and a study in Portugal indicated 17. 5% among university students and 10.1 % among households (13).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have drawn attention to the high rates of food insecurity experienced on college campuses, especially in high-income and low and middle income countries (8)(9)(10). In the USA an estimated average of 14.9% of college (11) students are at risk of being food insecure, about 38-48% in Australia (12) and 17% in Europe (13). Also, up to 65% of FI rates were reported among tertiary students in South Africa (14).…”
Section: Introductionmentioning
confidence: 99%
“…In any case, within European countries, the issue of FI among college and university students has not received as much focus compared to other regions globally, both before the pandemic [ 17 ] and in the context of the pandemic [ 18 ]. To address this gap in the literature, the present research, conducted from January to March 2022, aims to analyze the prevalence of FI and possible related factors among university students in Iceland during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%